Test of the aligned descriptor list for economic and social development : catalogue of index items - Organisation for Economic Co-operation and Development; Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1967)
This catalogue constitutes one of the elements of the test carried out on the Aligned descriptor list for economic and social development. It contains all references to the information which has been index and stored in the O.E.C.D.
usc 16/11/2021
Ref.
Keywords: International economic relations; Economic policy; Economic development; Economic assistance